4(x+3)-6=6+4x

Simple and best practice solution for 4(x+3)-6=6+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+3)-6=6+4x equation:


Simplifying
4(x + 3) + -6 = 6 + 4x

Reorder the terms:
4(3 + x) + -6 = 6 + 4x
(3 * 4 + x * 4) + -6 = 6 + 4x
(12 + 4x) + -6 = 6 + 4x

Reorder the terms:
12 + -6 + 4x = 6 + 4x

Combine like terms: 12 + -6 = 6
6 + 4x = 6 + 4x

Add '-6' to each side of the equation.
6 + -6 + 4x = 6 + -6 + 4x

Combine like terms: 6 + -6 = 0
0 + 4x = 6 + -6 + 4x
4x = 6 + -6 + 4x

Combine like terms: 6 + -6 = 0
4x = 0 + 4x
4x = 4x

Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| (13x-6)(13x-6)=117 | | (7x-8)(x-5)=(x-4)(8x-7) | | (x^8-3x^7)+(-x^6+3x^5)=0 | | (x+9)(x-2)=(x-1)(x+3) | | x-(-4+3x)=-8 | | 3x-(1/2)=2x+(7/4) | | 1/2=*/4 | | 1/2=*3 | | 16-4x-6=2x-x | | 49x^2+35x+6=0 | | x^4+6x^3=9x^2+54x | | x+(x+2)+(x+4)=189 | | 5(x+4)+(x-5)=10 | | (x^4+6x^3)+(-9x^2-54x)=0 | | 6z+z=-7z-9+2z | | 2.50x+39.99=1.75x+50.00 | | 6+16x-1=9x+93-4x | | -18+3=-5(x+2) | | -9=-7z-6(2z+1) | | 4x+22=40 | | -6z+4z=9z+2+5z | | 250x+39.99=1.75x+50.00 | | 4(n+2)+9=5-3n | | n-4n=6 | | 6(9+2x)=7x+14 | | -(-7n+3)=-(-2+6n) | | 3x^2+40x-75=0 | | 7w+6=3(w-6) | | 8+8t=-2(t-6) | | 9s^2+90s-125=0 | | 2+x/3=0 | | 5x-45=2x |

Equations solver categories